The Motif of the Royal Touch in Shakespeare’s „Macbeth”as a Symbol of Political Power - Szwach, Agnieszka (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2024)
The article analysis the phenomenon of the royal healing touch present in English culture of the Middle Ages and Early Modern period. It shows its development from the religious practice to the means of asserting political power and also engages in the discussion as to the role of the royal healing scene included in Shakespeare’s Macbeth.